PENENTUAN PARAMETER MODEL TANGKI DENGAN EMPAT SUSUNAN SERI PADA DAERAH ALIRAN SUNGAI ROKAN - Manyuk Fauzi; Yohanna Lilis Handayani; Annisa Destiany (Jurnal Infrastruktur, 2019)
Information about low flow and water availability is one of the important factors in the management of water resources. The Rokan River Basin as one of the water resources in Riau Province is very important to know the condition of its water availability. One conceptual hydrological model for low flow analysis is the Tank Model developed by Sugawara. Data input needed in this research is daily rainfall data at Pasar Tangun Station, climatology data at Rambah Utama station and discharge data at AWLR Pasir Pengaraian. Model parameter search in the calibration stage is by trial and error. Using a 90% confidence interval a range of parameter values for the tank model is obtained, which is special for production store are surface flow 150.81 mm ≤ H1 ≤ 204.75 mm, intermediate flow 156.74 mm ≤ H2 ≤ 194.37 mm, sub base flow 141.24 mm ≤ H3 ≤ 176, 54 mm and base flow 139.43 mm ≤ H4 ≤ 176.12 mm.